2019
DOI: 10.15408/es.v10i2.10239
|View full text |Cite
|
Sign up to set email alerts
|

An Effective of Pogil With Virtual Laboratory in Improving Science Process Skills and Attitudes: Simple Harmonic Motion Concept

Abstract: Simple harmonic motion is a concept that often involve complex and difficult equations, so that students can't construct knowledge of the concept. This research applies POGIL with a virtual laboratory, where students are encouraged to construct the concept and emphasize collaborative learning with different roles. Virtual laboratory allows students to explore and establish students' science process skills and attitude. This study used a quasi experiment with nonequivalent control group design. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
2
3
0
Order By: Relevance
“…The last result of the research is that there was an effect of the application of the POGIL learning model on students' observation skills and scientific attitudes. The results of this research are in line with (Alatas & Ziah, 2018) who state that the POGIL learning model has a good influence on students' science process skills. The POGIL learning model supports meaningfulness in learning so that students become more active during the observation activities.…”
Section: Discussionsupporting
confidence: 87%
“…The last result of the research is that there was an effect of the application of the POGIL learning model on students' observation skills and scientific attitudes. The results of this research are in line with (Alatas & Ziah, 2018) who state that the POGIL learning model has a good influence on students' science process skills. The POGIL learning model supports meaningfulness in learning so that students become more active during the observation activities.…”
Section: Discussionsupporting
confidence: 87%
“…From these results, it can be concluded that the POGIL model has an effect on students' process skills. This is in line with previous research which states that POGIL can improve science process skills for students (Alatas & Fachrunisa, 2018;Idul & B. Caro, 2022;Zamista & Kaniawati, 2015). The difference in process skills between the experimental class and the control class can be caused because, in the inquiry model learning, learning activities are not only in the form of knowledge transfer from teachers and students.…”
Section: Influence Of the Pogil Model On Students' Science Literacy A...supporting
confidence: 90%
“…Science process skills are one of the approaches to science learning that are very important for scientific investigation (Shahali & Halim, 2010;Kruea-In & Thongperm, 2014;Juhji, 2016;Alatas & Fachrunisa, 2018). Science process skills are interpreted as adaptations of skills used by scientists to compile knowledge, think about problems, and make conclusions (Karslı, Yaman, & Ayas, 2010).…”
Section: Introductionmentioning
confidence: 99%